2017
DOI: 10.4271/2017-01-2293
|View full text |Cite
|
Sign up to set email alerts
|

The Application of New Approaches to the Analysis of Deposits from the Jet Fuel Thermal Oxidation Tester (JFTOT)

Abstract: Studies of diesel system deposits continue to be the subject of interest and publications worldwide. The introduction of high pressure common rail systems resulting in high fuel temperatures in the system with the concomitant use of fuels of varying solubilizing ability (e.g. ULSD and FAME blends) have seen deposits formed at the tip of the injector and on various internal injector components. Though deposit control additives (DCAs) have been successfully deployed to mitigate the deposit formation, work is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There has also been extension of the use of the JFTOT technique by a number of groups [35 59-60] with Lacey et al correlating the deposit in the injector hardware with the deposit observed on the JFTOT tube. Bucholz [61] indicated its possible use as a preventative screen and Barker showed the wide variety of information which may be extracted from a tube deposit by modern analytical techniques [62].…”
Section: Excerpts From History: Analytical Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been extension of the use of the JFTOT technique by a number of groups [35 59-60] with Lacey et al correlating the deposit in the injector hardware with the deposit observed on the JFTOT tube. Bucholz [61] indicated its possible use as a preventative screen and Barker showed the wide variety of information which may be extracted from a tube deposit by modern analytical techniques [62].…”
Section: Excerpts From History: Analytical Testingmentioning
confidence: 99%
“…The ToF-SIMS [47, 52, 54, 55, and 56] technique and Principle Component Analysis PCA methodology [62], have been described elsewhere in isolation and in combination to analyse fuel deposits. Hence a brief description follows.…”
Section: Tof-sims/pca Analysis Field Samplesmentioning
confidence: 99%
“…Analysis methods such as scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) have been used in the aforementioned studies to investigate deposit composition and structure to provide insights on deposit formation mechanisms. Barker et al combined a number of techniques (fourier-transform infrared spectroscopy, profilometry, scanning electron microscopy, time of flight secondary ion mass spectroscopy, and direct analaysis in real time mass spectroscopy) to obtain morphological, chemical and compositional data from nozzles [13]. However, there remains a significant gap in knowledge when it comes to understanding the initial mechanism which causes fuel deposits to form on the nozzle surface.…”
Section: (1) Introductionmentioning
confidence: 99%